A Review of Fungal Disease in Hevea brasiliensis (Willd. ex A. Juss.) Mull. Arg.: From Identification to Scientific Investigation for Control Strategies - Fathia Ainusyifa; Retno Lestari; Ratna Yuniati (Jurnal Penelitian Pendidikan IPA, 2024)
Fungal diseases pose a substantial risk to the health and productivity of rubber plants (Hevea brasiliensis (Willd. ex ​ A. Juss.) Mull. Arg., the primary source of natural rubber. The diverse fungal pathogens responsible for these diseases lead to significant economic losses in rubber plantations, threatening the global rubber supply. This review provides a comprehensive examination of major fungal diseases affecting rubber plants, focusing on their identification, scientific analysis, and management strategies. Conventional methods for pathogen identification, while valuable, often lack the efficiency and precision required for effective disease control. Recent advancements in molecular diagnostics, genomics, and biotechnology have greatly improved the accuracy and speed of pathogen detection, enabling more targeted and sustainable management practices. Integrated pest management, mainly through the use of disease-tolerant clones, is emerging as a viable alternative to chemical fungicides. Although chemical fungicides remain the most widely used solution due to their accessibility and effectiveness, their environmental impact and potential for resistance necessitate a shift toward sustainable practices. While biofungicides offer a more environmentally friendly option and are already in use, they are currently limited to small-scale plantations and have yet to be adopted for large-scale production. Efforts to develop resistant clones through molecular studies and advanced cloning techniques are ongoing, representing the most sustainable approach for combating fungal diseases in rubber plantations. By synthesizing current knowledge and advancements, this review underscores the pressing challenges in managing fungal diseases and the opportunities presented by innovative technologies. The findings aim to guide future research and promote the development of efficient, sustainable strategies for maintaining rubber crop health, ensuring consistent production, and safeguarding the economic stability of the rubber industry.